HEADSHIP SCHOOL CLIMATE PROFICIENCY: AGENDA FOR IMPROVING ACADEMIC PERFORMANCE IN BOTSWANA - Bakokonyane, Kaone (African Journal of Education and Practice, 2022)
Purpose: The study examined how headship school climate proficiencies influenced the learner academic achievement of two high and two low performing primary schools of Kweneng region in Botswana. The purpose of the study was to identify the headship school climate proficiencies that influence learner acacdemic achievement and how the proficiencies influenced learner academic achievement in high and low performing rural primary schools of Kweneng Region. Methodology: Qualitative approach, using a multi-cross case study analysis was used. Data were collected through an in-depth, semi-structured and focus group interviews, observations and document analysis. Purposive sampling methods were used and the study drew data from fifty-six (56) participants. These were four school heads, four deputy school heads, four heads of department, eight senior teachers, twelve teachers and twenty-four learners. This study applied the Hargreaves Capital Theory of School Effectiveness and Improvement. The cross-analysis case study findings revealed that high performing rural primary schools had school climate proficiency. Findings: This approach helped them in cultivating a positive academic learning where listening to concerns of learners, teachers and stakeholders was possible. On the contrary, low performing schools paid lip service to "˜involvement' approach. The study, therefore, concludes that headship school climate proficiency enabled the school heads to gain trust of collaborators hence improving learner academic achievement. Unique contribution to theory, practice and policy: This study recommends that, school heads in rural areas should be trained in school climate proficiencies. This research could assist in the development of future professional development programmes for school heads in rural areas. Any future study that focuses on learner academic achievement in Botswana's rural secondary schools could consolidate or expand on the findings of this research.